Handbook of Clean Energy Systems 2015
DOI: 10.1002/9781118991978.hces089
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Residential Indoor Thermal Environment Control

Abstract: In this article, recent developments on the efficient control of residential indoor thermal environment are reported. Firstly, fundamental issues for indoor environmental control in residences are discussed. This is followed by presenting an analysis of a number of current control issues for direct expansion ( DX ) air‐conditioning (A/C) systems, including the capacity control, humidity control, and the inherent operating characteristics of a DX A/C system. A num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Song et al [37], carrying out CFD (computational fluid dynamics) simulations of wind and thermal environments in northern Chinese residential areas, observed that areas with low plot ratios and large ventilation corridors are more susceptible to the influence of water bodies. Research on the thermal environment of residential areas in waterfront regions is still limited, with some research results focusing on severely cold regions in China [38], regions with hot summers and cold winters [39], and regions with hot summers and mild winters [40]. There are significant variations in different climatic zones, and research on the thermal environment characteristics of residential waterfront areas in cold regions is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [37], carrying out CFD (computational fluid dynamics) simulations of wind and thermal environments in northern Chinese residential areas, observed that areas with low plot ratios and large ventilation corridors are more susceptible to the influence of water bodies. Research on the thermal environment of residential areas in waterfront regions is still limited, with some research results focusing on severely cold regions in China [38], regions with hot summers and cold winters [39], and regions with hot summers and mild winters [40]. There are significant variations in different climatic zones, and research on the thermal environment characteristics of residential waterfront areas in cold regions is still insufficient.…”
Section: Introductionmentioning
confidence: 99%